«Սասնա ծռեր» հերոսավեպի Մոկաց պատումների գրառման և հրատարակման պատմությունը - Պողոսյան, Աննա (Արմավ հրատ.)
Армянский народный героический эпос «Саснацрер» был обнаружен и записан в течение 19-20 веков. Был записан в Западной Армении, в частности, со слов сказителей живущих в бассейне озера Ван, а также в провинциях к юго-западу и северо-востокуот него: Сасун, Муш, Бахеш, Мокс, Шатах, Ван, Айоц-дзор, Хлат, Арчеш, Маназкерт, Алашкерт, Баязет. Они были малограмотными, благочестивыми крестьянами, которые были насильно выселены из своей родины во время Геноцида армянского народа и нашли пристанище в Восточной Армении (Вагаршапат, Аштарак, Апаран, Талин, Нор Баязет, Веди, Арташат, Ширак, Лори), Парскаайке (Хой, Салмаст и Маку), Тифлисе и пр., став переселенцами. Большая часть сказаний героического эпоса «Саснацрер» была записана именно в их новых поселениях․ Armenian folk heroic epos “SasnaTsrer” was discovered and recorded in course of the 19-20 centuries. It was recorded in the Western Armenia, in particular, according to oral information provided by storytellers living in the basin of Lake Van, as well as provinces located to the south-west and north-east of it: Sasun, Mush, Baghesh, Moks, Shatakh, Van, Hayotsdzor, Khlat, Archesh, Manazkert, Alashkert, Bayazet. They were uneducated, pious countrymen, who were forcefully resettled from their homeland during the Genocide of Armenians and found their shelter in the Western Armenia (Vagharshapat, Ashtarak, Aparan, Talin, Nor Bayazet, Vedi, Artashat, Shirak, Lori), Parskahayk (Khoy, Salmast, Maku), Tiflis, etc. becoming migrant settlers. So, most of the stories of the “SasnaTsrer” heroic novel were recorded in these new settlements.
Keywords: Գրականություն